Α‐Halogenoacetanilides as Hydrogen‐Bonding Organocatalysts that Activate Carbonyl Bonds: Fluorine versus Chlorine and Bromine. Issue 10 (12th February 2014) - Koeller, Sylvain; Thomas, Coralie; Peruch, Fréderic; Deffieux, Alain; Massip, Stéphane; Léger, Jean‐Michel; Desvergne, Jean‐Pierre; Milet, Anne; Bibal, Brigitte
Abstract α‐Halogenoacetanilides (X=F, Cl, Br) were examined as H‐bonding organocatalysts designed for the double activation of CO bonds through NH and CH donor groups. Depending on the halide substituents, the double H‐bond involved a nonconventional CH⋅⋅⋅O interaction with either a HCXn (n=1–2, X=Cl, Br) or a HCAr bond (X=F), as shown in the solid‐state crystal structures and by molecular modeling. In addition, the catalytic properties of α‐halogenoacetanilides were evaluated in the ring‐opening polymerization of lactide, in the presence of a tertiary amine as cocatalyst. The α‐dichloro‐ and α‐dibromoacetanilides containing electron‐deficient aromatic groups afforded the most attractive double H‐bonding properties towards CO bonds, with a NH⋅⋅⋅O⋅⋅⋅HCX2 interaction.